Non-ictal, interictal and ictal déjà vu: a systematic review and meta-analysis - Hadzic, Alena; Andersson, Stein (Frontiers in Neurology, 2024)
Background: Déjà vu, French for "already seen", is a phenomenon most people will experience at least once in their lifetime. Emerging evidence suggests that déjà vu occurs in healthy individuals (as "non-ictal déjà vu") and in epilepsy patient during seizures (as "ictal déjà vu") and between seizures (as "interictal déjà vu"). Although the ILAE has recognised déjà vu as a symptom of epilepsy, it is notably absent from the ICD-11. A lack of evidence-based research may account for this omission.To our knowledge, this study represents the first systematic review and meta-analysis on déjà vu experiences. Through detailed examinations of non-ictal, interictal and ictal déjà vu, we seek to highlight possible clinical implications. Rethinking the status quo of ictal déjà vu could potentially lead to earlier interventions and improve outcomes for epilepsy patients.Methods: This study was registered in PROSPERO (ID: CRD42023394239) on 2 February 2023. Systematic searches were conducted across four databases: EMBASE, MEDLINE, PsycINFO, and PubMed, from inception to 1 February 2023, limited to English language and human participants. Studies were included/excluded based on predefined criteria. Data was extracted according to the PICO framework and synthesised through a thematic approach. Meta-analyses were performed to estimate prevalence's of the phenomena. Study quality, heterogeneity and publications bias were assessed.Results: Database searching identified 1677 records, of which 46 studies were included. Metaanalyses of prevalence showed that non-ictal déjà vu was experienced by 0.74 (95% CI[0.67, 0.79], p < 0.001) of healthy individuals, whereas interictal déjà vu was experienced by 0.62 (95% CI[0.48, 0.75], p < 0.05) and ictal déjà vu by 0.22 (95% CI[0.15, 0.32], p < 0.001) of epilepsy patients. Examinations of phenomenological (sex, age, frequency, duration, co-occurring emotional valence and dissociative symptoms) and neuroscientific (brain structures and functions) data revealed significant variations between non-ictal, interictal, and ictal déjà vu on several domains. Conclusion: This systematic review and meta-analysis do not support the notion that non-ictal, interictal and ictal déjà vu are homogenous experiences. Instead, it provides insight for ictal déjà vu as a symptom of epilepsy that should be considered included in future revisions of the ICD-11.